Changes in Community Composition Induced by Experimental Warming in an Alpine Meadow: Beyond Plant Functional Type - Hu, Xiaoli; Zhou, Wenlong; Li, Xiaonuo; Niklas, Karl J.; Sun, Shucun (Frontiers in Ecology and Evolution, 2021)
Climate warming exerts profound effects on plant community composition. However, responses to climate warming are often reported at the community and functional type levels, but not at the species level. To test whether warming-induced changes are consistent among community, functional type, and species levels, we examined the warming-induced changes at different levels in an alpine meadow from 2015 to 2018. The warming was achieved by deploying six (open top) chambers (including three non-warmed chambers and three warmed chambers; 15 × 15 × 2.5 m (height) for each) that resulted in a small increase in mean annual temperature (0.3–0.5 °C, varying with years) with a higher increase during the non-growing season (0.4–0.6 °C) than in the growing season (0.03–0.47 °C). The results show that warming increased plant aboveground biomass but did not change species richness, Shannon diversity and evenness at the community level. At the functional type level, warming increased the relative abundance of grasses from 3% to 16%, but decreased the relative abundance of forbs from 89% to 79%, and the relative abundances of sedges and legumes were unchanged. However, for a given functional type, warming could result in contrasting effects on the relative abundance among species, e.g., the abundances of the forb species Geranium pylzowianum, Potentilla anserine, Euphrasia pectinate and the sedge species Carex atrofusca increased in the warmed (compared to the non-warmed) chambers. More importantly, the difference in species identity between warmed and non-warmed chamber revealed warming-induced species loss. Specifically, four forb species were lost in both types of chambers, one additional forb species (Angelica apaensis) was lost in the non-warmed chambers, and two additional species (one forb species Saussurea stella and one sedge species Blysmus sinocompressus) were lost in the warmed chambers. Consequently, changes at the species level could not be deduced from the results at the community or functional type levels. These data indicate that species-level responses to climate changes must be more intensively studied. This work also highlights the importance of examining species identity (and not only species number) to studying changes of community composition in response to climate warming.